Proportion of Helicobacter pylori Among Dyspeptic Patients Detected by Molecular Methods in a Teaching Hospital in Sri Lank - Ubhayawardana, D. L; Weerasekera, M. M; Weerasekera, D. D; Gunasekera, T. D; Fernando, S. S (My University, 2015)
Background: Infection with Helicobacter pylori is considered as a major cause of chronic gastritis, peptic ulcer disease and gastric cancer. More than half of the world’s population is infected with H. pylori. In Sri Lanka various groups have reported a prevalence ranging from 3% to 70% over the last decade. Objectives: The aim of this study was to determine the current proportion of H. pylori and risk factors for H. pylori infections. Patients and Methods: The study was a cross sectional, descriptive study in which 100 dyspeptic patients who were required to undergo endoscopy examination were included. The study was carried out at a Teaching Hospital in Sri Lanka. In-house urease test and PCR amplification of the glmM gene of H. pylori was performed to diagnose H. pylori infection. A questionnaire was filled to collect sociodemographic data from the dyspeptic patients. Results: Eighteen dyspeptic patients were positive for H. pylori by both in-house CLO (Campylobacter-like organism test) test and polymerase chain reaction (PCR). Ten of cases were male (18%) while eight were female (17%). There was no association between the demographic factors and risk of H. pylori infection. Conclusions: The proportion of H. pylori infections was found to be 18% in the study population. There was no significant association with H. pylori and the studied demographic factors.
Keywords: Helicobacter; Dyspepsia; Risk Factors; PCR